1999
DOI: 10.1002/(sici)1521-4141(199901)29:01<132::aid-immu132>3.3.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase Cθ, a selective upstream regulator of JNK/SAPK and IL-2 promoter activation in Jurkat T cells

Abstract: The predominant expression of protein kinase C (PKC) theta in T cells (J. Biol. Chem. 1993. 268: 4997-5004), its isoenzyme-specific ability to stimulate AP-1 transcriptional activity (Mol. Cell. Biol. 1996. 16: 1842-1850) and the recent discovery of its selective and antigen-dependent colocalization with the contact region between T cells and antigen-presenting cells (Nature 1997. 385: 83-89) suggest that, among the PKC family members, PKCtheta plays a specialized role in T cell activation. By investigating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
63
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(66 citation statements)
references
References 30 publications
3
63
0
Order By: Relevance
“…Indeed, PKC-␣, PKC-⑀ (27), and PKC- (28) have been demonstrated to regulate the activities of ERK and JNK, respectively, in T cells, and studies in smooth muscle cells have demonstrated that PKC-␦ is involved in regulating p38 activity (37). The ability of ␤-oxa 21:3n-3 to partially inhibit ERK, but not JNK activity is consistent with suppression of PKC-⑀, but not PKC-translocation.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Indeed, PKC-␣, PKC-⑀ (27), and PKC- (28) have been demonstrated to regulate the activities of ERK and JNK, respectively, in T cells, and studies in smooth muscle cells have demonstrated that PKC-␦ is involved in regulating p38 activity (37). The ability of ␤-oxa 21:3n-3 to partially inhibit ERK, but not JNK activity is consistent with suppression of PKC-⑀, but not PKC-translocation.…”
Section: Discussionmentioning
confidence: 78%
“…Several PKC isozymes have been demonstrated to regulate the activity of the MAP kinases and the production of lymphokines. PKC-␣ and PKC-⑀ have been shown to regulate ERK (27), whereas PKC-regulates JNK (28,29). To further characterize the reduction in PKC translocation, the ability of ␤-oxa 21:3n-3 and 22:6n-3 to inhibit individual isozyme translocation was examined.…”
Section: ␤-Oxa 21:3n-3 Inhibits Lymphocyte Function By Targeting Specmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have shown that among several PKC isoforms tested, only PKC was capable of significantly stimulating Ras-dependent transcription from an AP-1 element in EL4 leukemic T cells (10). PKC also specifically cooperates with calcineurin and plays a critical role in c-Jun NH 2 -terminal kinase activation and induction of the interleukin-2 gene (11,12). Recent reports indicated that among different T cell-expressed PKC isoforms, PKC was the only one to colocalize precisely with the TCR⅐CD3 complex in the contact region between antigen-specific T cells and antigen-presenting cells.…”
Section: Protein Kinase C (Pkc)mentioning
confidence: 98%
“…Furthermore, studies using pharmocological inhibitors and PKC antisense RNA and overexpression studies using dominant negative and constitutively active mutant proteins have established a role for PKC in activation of AP-1 (7) and NF-B (8,9). PKC also synergizes with calcineurin to activate NFAT and IL-2 transcription (10,11), and with Vav to mediate IL-4 gene expression in response to CD28 costimulation (12).…”
mentioning
confidence: 99%